Drought and heat stress studies in perennial ryegrass: a bibliometric analysis 1994–2024 - Wang, Rui; Gao, Yang; Li, Junqin; Wang, Xiangtao; Yang, Yuting; Huang, Haiyan; Zhou, Zijun; Wang, Puchang; Zhao, Lili (Frontiers in Sustainable Food Systems, 2024)
Perennial ryegrass (Lolium perenne L.) is a key forage species in warm temperate to subtropical regions worldwide. Climate change poses significant challenges to agriculture, particularly through drought and heat stress, which adversely affect ryegrass yield and may be further exacerbated by global warming. Despite numerous research achievements in recent years, a comprehensive bibliometric analysis of the literature on drought and heat stress in perennial ryegrass is lacking. This study provides a quantitative analysis of relevant literature published from 1994 to 2024, utilizing the Web of Science database to evaluate global research trends and priorities. The results indicate a consistent annual growth in publication output, with China and the United States being major contributors, and the journal Crop Science publishing the most papers. Keyword analysis shows that “growth,” “endophytic fungi,” and “yield” are most frequently used in drought stress research, while “growth,” “gene,” and “leaf” are common in heat stress research. Over the past 30 years, research has mainly focused on phenotype, response mechanisms, and drought and heat resistance techniques in perennial ryegrass. Endophyte have become a hot topic in drought stress research in recent years and have also gained attention in heat stress research, suggesting future research directions in this area. Furthermore, there is a need to strengthen research on the molecular mechanisms associated with drought stress in ryegrass, as well as to explore molecular responses to heat stress. The research trend shows increasing attention to the interaction between drought and heat stress, indicating it will become an important direction for future studies. The findings of this study offer valuable insights for guiding future research on perennial ryegrass under drought and heat stress conditions and provide useful information for researchers in related fields.